Identifying the Original Colour of the Paintwork on the Artistic and Industrial Recreation Pavilion Designed by Antonio Palacios for the Galician Regional Exhibition Held in 1909 - Patricia Sanmartín; Beatriz Prieto (Heritage, 2020)
The former Artistic and Industrial Recreation Pavilion, which was designed by Antonio Palacios (1874–1945) and built for the Galician Regional Exhibition held in 1909 in Santiago de Compostela (Galicia, north-western Spain), and which currently houses a nursery school, was completely restored in 2018. The main purpose of the restoration was to recover the original exterior colour of the building. For this purpose, a study was undertaken to identify the original colour of the paintwork by first consulting historical archives and then conducting a micromorphological analysis of stratigraphic paint samples by stereomicroscopic examination and scanning electron microscopy (SEM) coupled with electron dispersive spectroscopy (EDS). Three reformations of the building are documented: one carried out in 1926, when the metal roof was replaced with a tile roof; another conducted between 1967 (when the old pavilion was described as a "destroyed building") and the mid-1970s (when it began to be used as a nursery); and finally, another in 1981, when the building was repainted. The analytical results revealed layers of white or yellow ochre (vanilla) paint corresponding to different periods. The presence of titanium (Ti) in the paint was used as a marker of its age, as titanium white was first formulated in 1921. The original layers include Zn in their composition, indicating that zinc oxide (ZnO) was the pigment used in the “snow” white paint probably used on the building in its first years of existence. In all cases, the pigment base is lime mixed with silicates, kaolin and other clays.